Spectrum of Gastrointestinal Perforation in a Tertiary Hospital of North India - J. S., Shergill; S., Sharma; R, Kaur (International Journal of Innovative Research in Medical Science, 2018)
The commonest abdominal emergency is perforation of the gastro-intestinal tract. The surgical intervention for these has increased over the period of time. Drainage of the contaminated peritoneal fluid, repair of the perforation forms the surgical guidelines of the treatment. Aims & Objectives: To study the aetiology, clinical presentation, diagnostic aids and management of gastro intestinal perforations and factors if present leading to intestinal perforation including traumatic and nontraumatic. Material & Methods: The prospective study was conducted in the Department of General Surgery, Government Medical College, Amritsar, with 50 patients presenting in the surgical emergency. Provisional diagnosis was made from history and after clinical examination. Observations: Gastroduodenal perforations formed the major part, the age group of 21-30 years had the maximum patients, symptoms and signs of perforation were present in majority of the patients. The patients had septicaemia followed by wound infection and respiratory complications in the post-operative period. Conclusion: In the perforation of the gastrointestinal tract surgical treatment yields good results and decreases patient mortality.